Educação Profissional e Inclusão: possibilidades e limites para a constituição de uma educação inclusiva e emancipadora à luz da trajetória dos estudantes com deficiência egressos do IFCE - Felipe, Kelma de Freitas (2023)
The objective of this research was to analyze the repercussions of the professional qualification of people with disabilities, graduates of higher education courses at the Federal Instituto de Educacão do Ceará (IFCE), regarding the constitution of new inclusive and emancipatory social processes. Based on the thoughts of Gramsci (2004), this research discusses the educational formation of the subordinate class and the establishment of emancipatory processes; by Vygotsky (2021) and our theoretical constructs by researchers, such as Mantoan (2015), Lustosa (2021), Sassaki (2010), Nuernberg (2020) and Mello (2014) appropriating reflections on educational and labor processes of people with disabilities. As a methodology, it uses a qualitative approach, using interpretations mediated by the historical-dialectic method, combined with the Collective Subject Discourse technique by Lefèvre and Lefèvre (2021). In collecting information, the research collects official data on the level of education and insertion in the world of work based on data collected through the IBGE Census (2022), PNS (2019) and INEP (2021/2022); carries out the State of the Question on professional education, people with disabilities and the world of work; in addition to collecting information from students with disabilities who graduated from IFCE, graduated between the years 2008-2021, by applying questionnaires, made available online through the Surveymonkey tool, and conducting focus group interviews, through the Google Meet platform. As a result of this study, two important aspects were verified, among others: i) identification of inclusive social processes resulting from the access of people with disabilities to higher education courses and inclusion in the world of work; and ii) a notable absence of truly emancipatory education, considering that the educational processes established by the capitalist model of production do not promote interference in the economic and social structures established by the system. In this way, we infer from this investigation that the concept of emancipatory inclusion, from the perspective of human emancipation, is not present in this capitalist society. This research being an instrument for opening paths in search of the implementation of educational policies that provide the development of counter-hegemonic processes that enable social transformation.